Motivasi Dan Persepsi Wisatawan Digital Nomad Terhadap Kualitas Pelayanan Di BWork Bali Co-Working Space Kawasan Canggu, Kabupaten Badung - Sari, Komang Pretty Again Teja; Adikampana, I Made (JURNAL DESTINASI PARIWISATA; Vol 10 No 1 (2022): VOL 10, NO 1 (2022): (JANUARY - JUNE) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2022.v10.i01.p12, 2022)
Canggu area is the most popular nomad digital destination among nomad tourists, according to the Nomadlist version. The spread of digital nomad tourists has led to the emergence of co-working spaces with various facilities called Co-working Spaces. One of the Co-working Spaces that has just started operating in 2021, namely BWork Bali Co-working Space, is one of the most sought after by digital nomad tourists in Canggu area, Badung Regency. This study was conducted to determine the characteristics, motivations and perceptions of digital nomad tourists on the quality of service at BWork Bali Co-working Space Canggu Area, Badung Regency. This research was conducted by distributing a digital questionnaire in the form of a google form to 56 respondents of digital nomad tourists. The results showed that digital nomad tourists at BWork Bali Co-working Space based on their country of origin, namely the United States, worked as entrepreneurs, especially in the digital purview. The motivation of digital nomad tourists at BWork Bali Coworking Space got the highest score, namely on the driving variable towards Space and the pull factor on the Service and Quality variable. Meanwhile, the perception of digital nomad tourists on service quality at BWork Bali Co-working Space obtained Strongly Agree results with an average of 4.67 on Tangible, Empathy, Reliability, Responsive, and Assurance variables. Keyword:  service quality, co-working space, digital nomad, motivation, perception